2021
DOI: 10.3390/nu13010210
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+ Transporters in Digestive Cancers

Abstract: Despite magnesium (Mg2+) representing the second most abundant cation in the cell, its role in cellular physiology and pathology is far from being elucidated. Mg2+ homeostasis is regulated by Mg2+ transporters including Mitochondrial RNA Splicing Protein 2 (MRS2), Transient Receptor Potential Cation Channel Subfamily M, Member 6/7 (TRPM6/7), Magnesium Transporter 1 (MAGT1), Solute Carrier Family 41 Member 1 (SCL41A1), and Cyclin and CBS Domain Divalent Metal Cation Transport Mediator (CNNM) proteins. Recent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 114 publications
(160 reference statements)
0
14
0
Order By: Relevance
“…We have also demonstrated that Mg homeostasis in LoVo-R is maintained through the overexpression of Magnesium Transporter protein 1 (MagT1) and the downregulation of Transient Receptor Potential Cation Channel Subfamily M Member 7 (TRPM7), two ubiquitously expressed Mg transporters [13]. Notably, the involvement of Mg transporters is well documented in several types of digestive cancers including colorectal adenocarcinomas [14]. In the cell Mg is stored primarily in the mitochondria [15], and, interestingly, we described different structural organization of these organelles in LoVo-R vs. LoVo-S [10].…”
Section: Introductionmentioning
confidence: 97%
“…We have also demonstrated that Mg homeostasis in LoVo-R is maintained through the overexpression of Magnesium Transporter protein 1 (MagT1) and the downregulation of Transient Receptor Potential Cation Channel Subfamily M Member 7 (TRPM7), two ubiquitously expressed Mg transporters [13]. Notably, the involvement of Mg transporters is well documented in several types of digestive cancers including colorectal adenocarcinomas [14]. In the cell Mg is stored primarily in the mitochondria [15], and, interestingly, we described different structural organization of these organelles in LoVo-R vs. LoVo-S [10].…”
Section: Introductionmentioning
confidence: 97%
“…Zheng et al (13) stated that the high mRNA expression level of MAGT1 in colorectal cancer also indicated a poor prognosis. Notably, magnesium transporters have been shown to play an important role in digestive cancer (32). In addition, the magnesium transporter protein solute carrier family 41 member 1 was reported to suppress human pancreatic ductal adenocarcinoma (33).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the human body, Mg 2+ is mainly absorbed in the small intestine through paracellular transport and membrane transporters. Due to the poor expression of claudins in the small intestine, paracellular transport is the most common mechanism for magnesium transportation [ 247 ].…”
Section: H Pylori and Mineralsmentioning
confidence: 99%